Uma cidade em busca de turistas: limites e possibilidades do turismo em Nova Friburgo - Giolito, Osvaldo José Ramalho (2006)
This work intends to demonstrate how the reality reached by the immigrants from Switzerland and other countries, the geography, the natural beauties, the remaining cultural marks and the climage are aspects that positivetly differ Nova Friburgo from most of Rio de Janeiro’s state cities, conferring to it a privileged role in the tourist scene. Also supports the use of ambient’s analyses as permanent activities of the touristic planning, and, by the results obtained in surveys, suggests strategies that could generate significant increases in the obtained results by the tourism sector, facilitating the increase of investments, the envolvement of the population, and the joint action between the public power, the private initiative and the service sector, influencing positively the sustainable development of a potentially tourist city.